Navigating Linguistic Inequalities In E-Learning: English And Arabic In The Saudi Arabian Context - Ahmed Benyo (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study investigates the challenges and implications of linguistic inequalities in e-learning environments, focusing on the interplay between English and Arabic in the Saudi Arabian context. While English is frequently employed as the medium of instruction in higher education, Arabic remains the dominant language of cultural and social interaction. This linguistic imbalance creates barriers that affect students’ access to, and engagement with, digital learning platforms. To explore this issue, the research adopts a quantitative case study design involving 150 Saudi university students enrolled in various online learning programs. Data were collected through a structured questionnaire designed to measure students’ perceptions of language barriers, their learning experiences, and academic performance outcomes related to English- and Arabic-mediated e-learning platforms. The responses were analyzed using descriptive statistics (mean, standard deviation, frequency distributions) and inferential statistical methods, including independent sample t-tests and one-way ANOVA, to examine significant differences across variables such as proficiency level, academic discipline, and frequency of platform usage. Findings reveal that linguistic inequalities significantly shape students’ ability to comprehend course materials, participate in discussions, and achieve desired learning outcomes. English-dominant platforms were perceived as advantageous for students with higher proficiency but exclusionary for those with limited English competence, while Arabic-supported platforms facilitated inclusivity but were often limited in scope and resources.